2015
DOI: 10.1097/dcc.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

Proper Skin Preparation and Electrode Placement Decreases Alarms on a Telemetry Unit

Abstract: Proper skin preparation and ECG electrode placement reduced alarms. Reducing alarm frequency is vital to decreasing alarm fatigue and increasing patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Our results also showed that nurses do not follow the unit protocol (ie, every 24 hours and if needed) when changing leads; enforcement of this policy should take place [ 11 ]. In a telemetry unit, proper skin preparation and electrode placement resulted in a significant reduction of ECG alarms [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also showed that nurses do not follow the unit protocol (ie, every 24 hours and if needed) when changing leads; enforcement of this policy should take place [ 11 ]. In a telemetry unit, proper skin preparation and electrode placement resulted in a significant reduction of ECG alarms [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Care alerts are tailored and programmed at implant by the implanting physician, allowing for more appropriate patient alert management and decrease potential ''alert fatigue,'' which may affect workflow efficiency and patient safety. 11 The initial LINQt ILR patient cohort (20%) was added to our regular ''virtual'' clinic device group, under ''ILR Patients.'' Incoming daily wireless data resulted in data avalanche and RM management challenges, necessitating a strategy for categorizing specific diagnoses alerts to streamline data and provide appropriate clinical follow-up care.…”
Section: Patientmentioning
confidence: 99%
“…In numerous inpatient settings, implementing daily skin care and changes in electrode pads have resulted in a reduction in total nuisance alarms. [16][17][18][19][20] In the presence of excessive nonactionable cardiac monitoring alarms, something as basic as ensuring proper anatomic electrode placement can also make an impact. Even in a small study, a significant reduction in nuisance alarms could be demonstrated within the first 24 hours after initiation of a new protocol for electrode placement, which included evidence-based skin preparation prior to daily electrode changes.…”
mentioning
confidence: 99%
“…Even in a small study, a significant reduction in nuisance alarms could be demonstrated within the first 24 hours after initiation of a new protocol for electrode placement, which included evidence-based skin preparation prior to daily electrode changes. 19 Daily telemetry electrode change was one of the effective interventions introduced as part of a 2-year alarm management quality improvement (QI) project at a 580-bed hospital. 18 Strategies to address the issue of clinical alarm fatigue vary in scope.…”
mentioning
confidence: 99%
See 1 more Smart Citation